The Impact of Relational Marketing and Service Quality on Customer Loyalty: A Comprehensive Analysis - Mochtar Luthfi M; Muh Fajar MS; Hermawaty RK; Mahyus Mahyus; Muliati Muliati (PINISI Discretion Review, 2023)
This research aims to test and analyze: (1) The effect of relationship marketing on customer loyalty. (2) The effect of service quality on customer loyalty. (3) The simultaneous effect of relationship marketing and service quality on customer loyalty. (4) The extent of the contribution/influence of relationship marketing and service quality on customer loyalty. The type of research used is quantitative research with data collection techniques using exact sciences, namely through observation, questionnaires, and documentation, with data analysis techniques using multiple linear regression analysis using SPSS 24. The research results show that: (1) Relationship marketing has a significant influence on customer loyalty, with t_calculated = 4.026 > t_table 1.671 and a significance of 0.000. (2) Service quality has a significant influence on customer loyalty, with t_calculated = 5.336 > t_table 1.671 and a significance of 0.000. (3) Relationship marketing and service quality simultaneously have a significant influence on customer loyalty, with f_calculated = 115.170 > f_table 3.16, and a significance of 0.000. (4) Relationship marketing and service quality contribute 80.2% or 0.802 to customer loyalty.